The raid : redemption - Evans, Gareth; Sagantaro, Ario; Uwais, Iko; Taslim, Joe; Alamsyah, Donny (Indonesia : Pt.Merantau Films, 2011)
Rama, a member of a special force team, arrives at a rundown apartment block with a mission to remove its owner, a notorious drug lord. The building has become a sanctuary to killers, gangs, rapist and thieves seeking accommodation in the one place they know they cannot be touched by the police. When a spotter blows their cover, Rama and his team must fight their way through every floor and every room not just to complete their mission but to survive their bloody ordeal.
Bonus: Behind the scenes ; photo gallery.
Music by Mike Shinoda and Joseph Trapanese ; director of photography, Matt Flannery ; executive producer Rangga Maya, Barack-Evans, Irwan D. Mussry, Nate Bolotin and Todd Brown.
Iko Uwais, Joe Taslim, Donny Alamsyah, Yayan Ruhian, Pierre Gruno, Tegar Satrya and Ray Sahetapy.
LPF: 18
DVD format, MPEG, PAL, Surround 5.1, Region 3.
Winner: Toronto International Film Festival 2011, Audience Choice Midnight Madness Award.
Keywords: Crime films; Police films; Thriller (Motion pictures).; Gangsters -- Indonesia -- Drama; Gangster films